PELUANG DAN TANTANGAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI ERA DIGITAL - Yahya, Agil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the opportunities and challenges of digital transformation in Islamic Religious Education (PAI) learning in Indonesia. Digital technology presents many opportunities, such as wider access to information and learning resources, more interactive and collaborative learning, flexibility through distance learning, and innovation in assessment methods. However, on the other hand, this digital transformation also presents a number of challenges, including the quality and reliability of information from the internet, the diminishing of spiritual and ethical aspects, the digital divide in 3T (frontier, remote and underdeveloped) areas, and educators’ difficulties in adapting to technology. This article underscores the importance of developing educational policies that support the equitable and sustainable adoption of technology, as well as appropriate training for educators so that PAI learning can maximize the potential of digital technology. Thus, technology integration in religious education must be carefully designed to balance the benefits of digitalization and the maintenance of spiritual values in PAI education.